1981
DOI: 10.1042/bj1950159
|View full text |Cite
|
Sign up to set email alerts
|

Purification of rabbit bone inhibitor of collagenase

Abstract: 1. Rabbit bones in tissue culture synthesize an inhibitor of collagenase during the first 4 days of culture. 2. The inhibitor was purified by a combination of gel filtration, concanavalin A--Sepharose chromatography, ion-exchange chromatography and zinc-chelate affinity chromatography. 3. The purified inhibitor migrated as a single band on sodium dodecyl sulphate/polyacrylamide-gel electrophoresis and had a mol.wt. of 28000. 4. The inhibitor blocked the activity of the metalloproteinases collagenase, gelatinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
126
0
2

Year Published

1984
1984
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 338 publications
(133 citation statements)
references
References 25 publications
5
126
0
2
Order By: Relevance
“…All members of the TIMP family are characterized by their ability to inhibit MMP activity by forming essentially irreversible 1:1 molar stoichiometric complexes with the active enzymes (20,30). However, the association of TIMPs with the proforms of the MMPs is more specific, and so far only two such interactions have been described: that of TIMP-2 with the proform of gelatinase A (22,(33)(34)(35) and that of TIMP-1 with the proform of gelatinase B (13,45).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All members of the TIMP family are characterized by their ability to inhibit MMP activity by forming essentially irreversible 1:1 molar stoichiometric complexes with the active enzymes (20,30). However, the association of TIMPs with the proforms of the MMPs is more specific, and so far only two such interactions have been described: that of TIMP-2 with the proform of gelatinase A (22,(33)(34)(35) and that of TIMP-1 with the proform of gelatinase B (13,45).…”
Section: Discussionmentioning
confidence: 99%
“…2 Matrix metalloproteinase activity in the extracellular matrix is regulated by a family of specific inhibitors known as TIMPs (tissue inhibitor of metalloproteinases). Until recently, three members of this family had been characterized: TIMP-1 (20,21), TIMP-2 (22,23), and TIMP-3 (24,25). The N domains of these proteins share structural similarities (26 -28) and inhibit the activity of the MMPs by forming a 1:1 molar stoichiometric complex with the active enzyme, which is essentially irreversible (20,29,30).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We identified an erythroid-potentiating activity (EPA) in the supernatant of the HTLV-II-transformed human T-lymphblast cell line (Me), and purified the 28 000 Da glycoprotein molecule to homogeneity [5,16]. Subsequent eDNA cloning demonstrated that EPA was identical to tissue inhibitor of metalloproteinases (TIMP, TIMP-1) [17,18], which can be isolated from a variety of human tissues and body fluids and which has been shown to inhibit the eollagenase family of enzymes [19][20][21]. The purified natural EPA and, subsequently, the recombinant EPA were shown to augment colony formation by human CFU-E, BFU-E and K-562 cells [16,17,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Once active, collagenase, and indeed all of the MMPs, can be inhibited by a,-macroglobulin (a2M) (6), or by the more specific tissue inhibitor of metalloproteinases (TIMP) (7). TIMP is a glycoprotein of M, 28,000 containing 12 cysteine residues which form 6 disulfide bonds (8).…”
mentioning
confidence: 99%